Abstracts (Edited by Prof. Tahir Mahmood) - Mahmood, Tahir (Pakistan Journal of Ophthalmology, 2009)
The association between thyroid problems and glaucoma Cross JM, Girkin CA, Owsley C, McGwin Jr G Br J Ophthalmol 2008; 92:1503-5. Hydroxychloroquine retinopathy screening Semmer AE, Lee MS, Harrison AH, Olsen TW Br J Ophthahno1 2008; 92: 1653-5 Apodized diffractive versus refractive multifocal intraocular lenses: Optical and visual evaluation Zelichowska B, Rekas M, Stankiewicz A, Cervmo A, Montes-Mic6 R J Cataract Refract Surg. 2008; 34: 2036-42. Contrast sensitivity after refractive lens exchange with diffractive multifocal intraocular lens implantation in hyperopic eyes Ferrer-Blasco T, Montes-Mico R, Cervifio A, Alfonso JF, Fernandez-Vega L J Cataract Refract Surg. 2008; 34: 2043-8.